2017
DOI: 10.18632/oncotarget.14991
|View full text |Cite
|
Sign up to set email alerts
|

Surgery-induced monocytic myeloid-derived suppressor cells expand regulatory T cells in lung cancer

Abstract: While monocytic myeloid-derived suppressor cells (M-MDSCs) have been reported to induce the development of regulatory T cells (Treg), little is known about their correlation with Treg during perioperative period. Here, we demonstrated that the M-MDSCs expressing CD11b+CD33+HLA-DR–CD14+ in lung cancer patients after thoractomy significantly increased in comparison with preoperation, and their accumulation linearly correlated with an increase in Treg. Surgery-induced M-MDSCs, in addition to have high arginase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 23 publications
0
44
0
Order By: Relevance
“…Furthermore, a previous study has found that M-MDSCs were significantly increased after surgery. Besides, CD33 is involved in inhibiting T cells proliferation and affecting the development of Treg cells, and it is also involved in identifying tumor cells [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous study has found that M-MDSCs were significantly increased after surgery. Besides, CD33 is involved in inhibiting T cells proliferation and affecting the development of Treg cells, and it is also involved in identifying tumor cells [20] .…”
Section: Discussionmentioning
confidence: 99%
“…TAM regulates immune responses by recruiting Treg into the tumor microenvironment [121]. TAMs are known to recruit natural Treg into tumor tissues by producing chemokines (CC-chemokine ligands: CCL3, CCL4, CCL5, CCL20, CCL22) [122]. Furthermore, by producing IL-10 and TGF-β, TAM activates the transcription factor Foxp3 of CD4+ T cells, possibly contributing to the induction of inducible Treg [121,123].…”
Section: Tumor-associated Macrophages (Tams) and Tumor Immunitymentioning
confidence: 99%
“…Such a state of chronic inflammation may stimulate tumor progression. Furthermore, TAM induces cancer cell migration, infiltration, intravascular invasion and neovascularization needed for tumor growth, and this can lead to tumor metastasis [122]. For example, in breast cancer, CSF-1 secreted from cancer cells and vascular endothelial growth factor (VEGF) secreted from TAM mutually stimulate the secretion of these factors, resulting in the acceleration of tumor infiltration and intravascular invasion [125].…”
Section: Tumor-associated Macrophages (Tams) and Tumor Immunitymentioning
confidence: 99%
See 2 more Smart Citations